1997
DOI: 10.1152/ajpheart.1997.273.4.h1994
|View full text |Cite
|
Sign up to set email alerts
|

NO contributes to neurohypophysial but not other regional cerebral fluorocarbon-induced hyperemia in cats

Abstract: The large increase in cerebral blood flow (CBF) after fluorocarbon (FC)-exchange transfusion is thought to be caused by low oxygen content, decreased viscosity, or direct vasodilatory effect of the FC perfusate. The aim of this study was to determine whether nitric oxide (NO)-mediated vasorelaxation is increased in FC-perfused hemoglobin (Hb)-free cats because NO is not scavenged by Hb. We measured regional CBF with radiolabeled microspheres in three groups of anesthetized mechanically ventilated cats. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Blood flow results in the neurohypophysis, in which the blood vessels are highly permeable and NO exerts a tonic vasodilatory effect (37), offer a useful contrast with the rest of the brain. Whereas L-NAME decreased blood flow in both the cerebrum and neurohypophysis, Hb transfusion decreased blood flow only in neurohypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow results in the neurohypophysis, in which the blood vessels are highly permeable and NO exerts a tonic vasodilatory effect (37), offer a useful contrast with the rest of the brain. Whereas L-NAME decreased blood flow in both the cerebrum and neurohypophysis, Hb transfusion decreased blood flow only in neurohypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, NOS inhibitors do not always seem to increase myocardial oxygen consumption (42,49,68,76); the reasons for this discrepancy are not clear, although in some cases they are likely to relate to differences in the intracellular location, local concentration, permeability and K i of different inhibitors. Interestingly, no effect has been seen of NOS inhibitors on either oxygen consumption (44,69) or the redox state of cytochrome oxidase (30) in the anesthetized brain, even in the absence of potentially NO scavenging red blood cells (90).…”
Section: The Reality Of Inhibition?mentioning
confidence: 99%
“…Wagner et al (1997) observed a large increase in cerebral blood flow (CBF) in the hemispheres, brain stem, cerebellum, thalamus, and white matter after fluorocarbon (FC)-exchange transfusion in cats. They have shown that l-NAME inhibits brain NOS activity in FC-perfused cats, but does not reverse FC-exchange transfusion-induced CBF [ 54 ]. Kaufmann et al (2004) [ 55 ] assessed the effect of simultaneous inhibition of eNOS and nNOS on myocardial blood flow (MBF) and coronary flow reserve (CFR) in volunteers and in (denervated) transplant recipients.…”
Section: Introductionmentioning
confidence: 99%